Evaluation of the Antibacterial and Wound Healing Activity of Quercus persica - Akram, Ebrahimi; Masoud, Khayami; Vahid, Nejati (Journal of Basic & Applied Sciences, 2012)
Quercus persica is one of the four species oak that growing in the zagrossian region in Iran. This plant contains different components of therapeutic value. In this investigation, antibacterial and wound healing effects of methanolic extract of fruits of Quercus persica has been studied. Milled oak fruit that their hull was separated, was extracted with methanol in Soxhleťs apparatus .The effect of extract in three concentration (25,50,75mg/ml) were tested using agar diffusion method on Staphylococcus aureus ATCC 25923, Staphylococcus epidermidis RTCC 1898 and Escherichia coli O157:H7 and in form topical administration on excision wound in rats.Results showed that all of concentrations were effective on inhibition of bacteria, but this effect with 50 and 75 mg/ml concentration of extract was significant for bacteria. Also in comparison with tested antibiotics, the effect of 75 mg/ml concentration of extract was similar or higher than them. Also in the extract-treated wounds indicated that epithelialize faster, and the rate of wound contraction was significantly increased in comparison to control wounds. This results suggest that Quercus persica possesses compounds with antibacterial and wound healing properties